(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Traditional hypothesis testing may cause delay to take important decisions, as it depends on collecting a lot of evidence before conclusions are drawn. An alternative method for assessing software reliability is the sequential analysis, the Sequential Probability Ratio Test (SPRT). SPRT provides the mechanism of continuous monitoring which made it possible to attribute reliable or unreliable software rapidly. A framework of SPRT is proposed by Wald for different probability distributions. This paper proposed to use SPRT on ungrouped software failure data of six datasets collected from literature categorized as ungrouped with two popular S-shaped models. Real Valued Genetic Algorithm is proposed for parameter estimation to assess the performance evaluation.